Neuroprotective and Haematological Effects of Hydrochlorothiazide in Traumatic Brain Injury: Insights from a Rat Model Study - Bulama, Ibrahim; Sanda, Kyari Abba; Usman, Bello; Madziga, Hana A.; Waziri, Ali; Farouk, Umar Saidu; Suleiman, Nasiru; Monguno, Modu Bulama; Mshelia, Peter Anjili; Majama, Yagana Bukar; Dankoly, Sani M.; Bashir, Abdulfatah; et al. (Sahel Journal of Life Sciences FUDMA, 2024)
This study evaluated the effects of hydrochlorothiazide (HCT) on neurological and haematological abnormalities in albino rats induced with traumatic brain injury (TBI). Three groups of five rats each were used: Group 1 received HCT treatment (25 mg/kgbw) for 14 days post-TBI, Group 2 was TBI-induced but not treated, and Group 3 served as the non-traumatic non-treatment control. Neurological score, blood parameters (neutrophils, lymphocytes, monocytes, HB, PCV, WBC, RBC, the neutrophil/lymphocyte ratio, plasma glucose levels), serum electrolytes, and brain histology were assessed. HCT treatment significantly improved neurological scores and adaptability compared to the untreated TBI group. Plasma glucose levels in the treated group were lower in the first three hours post-induction but showed no difference from the untreated group on days two through five. The untreated TBI rats had significantly reduced RBC, HB, and PCV values, while the HCT-treated rats had higher values. The untreated group also showed higher counts of WBC, neutrophils, and lymphocytes, which were lower in the treated group. The neutrophil/lymphocyte ratio increased in the untreated group but decreased in the treated group. Electrolyte imbalances in the untreated group were corrected in the HCT-treated group. Histological analysis revealed more severe brain lesions in the untreated TBI group than in the treated group. In conclusion, HCT therapy reduces the inflammatory response induced by TBI and improves neurological function in albino rats.